2013
DOI: 10.1080/00380768.2013.844078
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of soil humic acids by preparative polyacrylamide gel electrophoresis in the presence of concentrated urea

Abstract: To separate soil humic acids (HAs) into their constituents and characterize them, polyacrylamide gel electrophoresis (PAGE) was carried out in the presence of 7 M urea using a preparative electrophoresis system. Two types of soil HAs were fractionated into nine fractions by PAGE. The dark-colored constituents were recovered from the electrophoretic fractions by precipitation on acidification, and the brown-colored constituents dissolved in the acidic solution of fast-moving fractions were recovered by adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…These results indicated that the acid-soluble constituents of HA were characterized by a low degree of humification and that their dissociation from HA resulted in an increase in the humification degree of precipitated constituents. These findings were in agreement with our previous study, where preparative PAGE of HAs was carried out in the presence of concentrated urea [7]. The degree of humification of the precipitated fraction was significantly higher when treated with alkaline concentrated urea.…”
Section: Humification Degree Of the Fractionssupporting
confidence: 83%
See 4 more Smart Citations
“…These results indicated that the acid-soluble constituents of HA were characterized by a low degree of humification and that their dissociation from HA resulted in an increase in the humification degree of precipitated constituents. These findings were in agreement with our previous study, where preparative PAGE of HAs was carried out in the presence of concentrated urea [7]. The degree of humification of the precipitated fraction was significantly higher when treated with alkaline concentrated urea.…”
Section: Humification Degree Of the Fractionssupporting
confidence: 83%
“…The DAX-8-non-adsorbed fraction (>1 kDa) showed a similar molecular size to that observed for the DAX-8-adsorbed fraction; however, the intensity of the peak was observed to be relatively lower. The molecular sizes of the acid-soluble constituents dissociated by concentrated urea treatment were similar to those dissociated by preparative PAGE in the presence of concentrated urea [7].…”
Section: Molecular Size Distribution Of the Fractionsmentioning
confidence: 49%
See 3 more Smart Citations